2016
DOI: 10.4236/ojst.2016.612033
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydroxide in Endodontics: An Overview

Abstract: Background: Calcium hydroxide has been used in dentistry since several decades. It has been used in a number of applications in the field of endodontics such as root resorption, intracanal medicament, and root canal sealers. Although this material exhibits several advantages, it also has some limitations. Objectives: To review the role of calcium hydroxide in the field of endodontics, focusing on its mechanism of action, antimicrobial effects, different applications, cytotoxicity or biocompatibility, and its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 29 publications
(45 reference statements)
0
46
0
1
Order By: Relevance
“…According to Ba-Hattab et al ,[ 15 ] The hydroxyl ions release in an aqueous environment is necessary for antimicrobial activity of calcium hydroxide. Hydroxyl ions react intensively with biomolecules because of their free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ba-Hattab et al ,[ 15 ] The hydroxyl ions release in an aqueous environment is necessary for antimicrobial activity of calcium hydroxide. Hydroxyl ions react intensively with biomolecules because of their free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Since its use in dentistry in 1921, calcium hydroxide has been considered the gold standard for direct pulp capping (36) . calcium hydroxide promotes hard bridge formation slowly, dissolves rapidly after marginal leakage and may dissolve during acid etching before the resin filling, and it does not chemically associate with the tooth or with the restored resin (37) .…”
Section: Discussionmentioning
confidence: 99%
“…The formation of hard tissue occurs at the contact area of necrotic tissue and inflamed tissue (39) . Under the necrosis layer, the pulpal stem cells differentiate into the odontoblast like cells, as a tissue reaction, and the dentin bridge matrix is placed (37) .…”
Section: Discussionmentioning
confidence: 99%
“…Calcium hydroxide has a wide range of antibacterial activities against oral pathogens [22]. The antimicrobial activities of calcium hydroxide are damaging to the bacterial membrane, protein denaturation, and damaging to the DNA [23]. Javidi et al reported that calcium hydroxide was able to reduce intraluminal and intratubular pathogens significantly in treated tooth [24].…”
Section: Discussionmentioning
confidence: 99%